VIRTUE ETHICS KOMUNIKAN BAGI WARGA INTERNET DI ERA DIGITAL DALAM PERSPEKTIF AL-QUR’AN - Irfan Afandi (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2024)
The digital era has shaped a boundless space for communication, which necessitates the cultivation of virtue ethics among communicators as members of the internet community (netizens). The QurÃ¢â‚¬â„¢an, as the holy scripture, provides guidance addressing human needs. This article discusses this issue, focusing on a thematic interpretation of QurÃ¢â‚¬â„¢anic verses, specifically Qs. An-Nur: 11Ã¢â‚¬â€œ20. Three main aspects are examined in this study: the ethical values to be developed by communicators, the good practices that can be implemented, and the consequences faced by communicators both in this world and in the hereafter. The method employed for interpreting these verses utilizes thematic exegesis based on QurÃ¢â‚¬â„¢anic texts. The data consist of literature drawn from classical and modern exegetical works, and the analytical tool used is content analysis. The study finds that the ethical values for communicators in digital spaces include maintaining husn al-dhann (positive presumption), ensuring that any information shared is grounded in established legal principles, and applying the principle of tabayyun (verification) in cases of social issues, as well as upholding politeness in communication. Good practices derived from the exegetical study include consistently verifying information upon receiving news, refusing to engage in discussions about false information, and having the courage to state, Ã¢â‚¬Å“It is not appropriate for us to talk about this.Ã¢â‚¬Â In practical terms, communicators in social media spaces should refrain from hastily clicking and sharing news whose veracity is uncertain or about which they lack sufficient knowledge. Finally, communicators who neglect the ethical code of conduct face consequences both in this world and the hereafter. In this world, the repercussions manifest as logical consequences of their actions, such as social fragmentation, discomfort, and even social conflict. In the hereafter, the punishment is a severe torment in hell. Therefore, it is imperative for communicators in digital spaces to uphold these moral values to attain safety and well-being both in this world and in the hereafter.